CONSIDERING AL-GHAZALI'S PHILOSOPHY THINKING AUTHORITY - Teguh Purnomo Putra (Mimbar Agama Budaya, 2021)
Abstract. The reputation and authority of al-Ghaza li in Islamic thought has had a profound influence as well as is controversial and ambivalent. His character covers almost all scientific disciplines in Islam. In the field of philosophy, the response to his thinking generated controversy that lasted for centuries. On the one hand, he is assumed to be a central figure for the decline of Islamic thought, especially philosophy, and is considered the most successful thinker in positioning philosophy proportionally in the Islamic world on the other. This paper discusses the philosophical thinking of al-Ghaza li, his criticisms of the thoughts of previous philosophers, and responses to his thoughts in the hope that they can provide conclusions that are quite "fair" and proportionate in positioning al-Ghazali in the islamic philosophy discourse. Abstrak. Reputasi dan otoritas al-Ghazali dalam jagad pemikiran Islam memiliki pengaruh yang begitu besar sekaligus kontroversial dan ambivalen. Ketokohannya meliputi hampir seluruh diskursus disiplin keilmuan dalam Islam. Dalam bidang filsafat, respons terhadap pemikirannya menuai kontroversi yang beralangsung berabad-abad. Satu sisi ia diasumsikan sebagai tokoh sentral atas kemunduran pemikiran dalam Islam, terutama filsafat, dan dianggap sebagai pemikir yang paling sukses dalam memposisikan filsafat secara proporsional dalam dunia Islam di sisi lain. Tulisan ini membahas tentang pemikiran filsafat al-Ghazali, kritik-kritiknya terhadap pemikiran filosof-filosof sebelumnya, dan respons terhadap pemikirannya dengan harapan bisa memberikan kesimpulan yang cukup “adil” dan proporsional dalam memposisikan al-Ghazali dalam diskursus filsafat Islam.